2009
DOI: 10.1007/s10452-009-9259-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of pumping rate of Chironomus plumosus larvae in natural burrows

Abstract: This paper investigates and compares experimentally determined water velocity field above natural macrozoobenthos burrows generated by Chironomus Plumosus larva during their bio-irrigation activity. All experiments were carried out using particle image velocimetry and performed in mesocosms filled with sediment burrowed by larvae, and the water velocity fields near the inlets and outlets of the U-shaped burrows were measured. From water velocity data the average volumetric flow rates between 54.6 and 61.1 mm 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…This work showed that A. stuartgranti is quite sensitive to artificial flows, responding to flows with velocities as low as ∼1 mm s , which is slower than those generated by copepods and copepodids (van Duren and Videler, 2003;Catton et al, 2007), tethered krill (Yen et al, 2003), midge larvae in burrows (Morad et al, 2010), and the tethered brine shrimp used with A. stuartgranti in prior studies (Schwalbe et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This work showed that A. stuartgranti is quite sensitive to artificial flows, responding to flows with velocities as low as ∼1 mm s , which is slower than those generated by copepods and copepodids (van Duren and Videler, 2003;Catton et al, 2007), tethered krill (Yen et al, 2003), midge larvae in burrows (Morad et al, 2010), and the tethered brine shrimp used with A. stuartgranti in prior studies (Schwalbe et al, 2012).…”
Section: Discussionmentioning
confidence: 82%
“…Flow rates were calculated as V ¼ _ Q= A, where V is water velocity, _ Q is flow rate (controlled by the digital settings of the pump, in ml min −1 ) and A is the internal cross-sectional area of the tubing (31.67 mm 2 ). The pump flow rates selected based on this equation were 1.9, 4.8, 9.5, 19.0 and 38.0 ml min burrow (∼14 mm s −1 ; Morad et al, 2010) and tethered adult brine shrimp (2-7 mm s −1 ; Schwalbe et al, 2012). Digital particle image velocimetry (DPIV) was used to analyze the water flowing from the active holes.…”
Section: Generation and Visualization Of Artificial Flowsmentioning
confidence: 99%
“…As a result, chironomids can be very efficient filter feeders, transporting significant amounts of particulate organic matter and nutrients into the sediment. Chironomids drastically reduce particle densities in the burrow outlet fluid compared to the inlet fluid (Morad et al 2010). Based on known pumping rates, filtration effects at the lake-wide scale might be comparable to the increased water clarity and shifts in phytoplankton communities associated with expanding dreissenid mussels (Strayer 2009).…”
Section: Filtration and Food Competition Between Pelagic Zooplanktonmentioning
confidence: 99%
“…The mechanism and rate by which infauna ventilate burrows vary considerably within and among taxonomic groups. Many polychaetes and insect larvae use muscular sinusoid undulations or peristaltic movements of the body to move water head-or tailwards in the burrow (Barrow & Wells 1982, Riisgård & Larsen 2005, Morad et al 2010. Bivalves, heart urchins and some polychaetes are dependent on ciliary action (Specht & Lee 1989, Riisgård & Larsen 2005, while many crustaceans use forceful beating of pleopods to create the water currents (Forster & Graf 1995.…”
Section: Burrow Ventilation and Bioirrigationmentioning
confidence: 99%